Development of a multi-criteria spatial planning support system for growth potential modelling in the Western Cape, South Africa. (January 2016) - van Niekerk, Adriaan; du Plessis, Danie; Boonzaaier, Ilze; Spocter, Manfred; Ferreira, Sanette; Loots, Lieb; Donaldson, Ronnie
Highlights: We address the ill-structured problem of growth potential modelling of settlements. A new framework for selecting and analysing growth potential criteria is proposed. A new settlement growth potential planning support system (GPPSS) was developed. The GPPSS is used to generate a range of growth scenarios of settlements for the study area. We show how the GPPSS can be used to select the most appropriate development policy solution. Abstract: Growth potential modelling is useful as it provides insight into which settlements in a region are likely to experience growth and which areas are likely to decline. However, growth potential modelling is an ill-structured problem as there is no universally-agreed set of criteria (parameters) that can be combined in a particular way (rules) to provide a definitive growth potential measure (solution). In this paper we address the ill-structured problem of growth potential modelling by combining multi-criteria decision making (MCDM), geographical information systems (GIS) and planning support systems (PPS) to generate a number of growth scenarios for settlements in Western Cape province of South Africa. A new framework and methodology for selecting, structuring and analysing multiple growth potential criteria is proposed. The framework, based on the principles of innovation potential and growth preconditions, was applied to demonstrate how it can be used to identify a series of candidate criteria relating to the growth potential of settlements. The criteria were subjected to a MCDM process involving criteria selection, weighting and normalisation. Two criteria sets, weighting schemes and normalisation methods were considered. Two different classification techniques were also evaluated. A total of 16 scenarios were generated using a newly-developed growth potential PPS (GPPSS). The paper shows how the GPPSS can be used to quantitatively and qualitatively assess the various scenarios and to select the most appropriate solution.